Prevalence of Long COVID-19 Symptoms After Hospital Discharge in Frail and Robust Patients - Damanti, Sarah; Cilla, Marta; Cilona, Maria; Fici, Aldo; Merolla, Aurora; Pacioni, Giacomo; De Lorenzo, Rebecca; Martinenghi, Sabina; Vitali, Giordano; Magnaghi, Cristiano; Fumagalli, Anna; Gennaro Mazza, Mario; et al. (Frontiers in Medicine, 2022)
Background: A motley post-acute symptomatology may develop after COVID 19, irrespectively of the acute disease severity, age and comorbidities. Frail individuals have reduced physiological reserves, and manifested a worse COVID-19 course, during the acute setting. However, it is still unknown, whether frailty may subtend some long COVID-19 manifestations. We explored the prevalence of long COVID-19 disturbs, in COVID-19 survivals. Methods: Observational study. Patients aged 65 or older followed up 1, 3 and 6 months after hospitalization for COVID-19 pneumonia. Results: 382 patients. Frail patients, were more malnourished (median Mini Nutritional Assessment Shor Form score 8 versus 9, p = 0.001), at higher risk of sarcopenia (median SARC-F score 3 versus 1.5, p = 0.003) and manifested a worse physical performance (median Short Physical Performance Battery (SPPB) score 10 versus 11, p = 0.007) than robust individuals, after hospital discharge following SARS-CoV-2 pneumonia. Frailty was a significantly associated with i) confusion, as a presenting symptom of COVID-19 (OR 77.84, 95% C.I. 4.23 – 1432.49, p = 0.003) , ii) malnutrition (MNA-SF: adjusted B -5.63, 95% C.I. -8.39 - -2.87, p < 0.001), risk of sarcopenia (SARCF: adjusted B 9.11, 95% C.I. 3.10 – 15.13, p = 0.003), impaired muscle performance (SPPB: B -3.47, 95% C.I. – 6.33 – 0.61, p =0.02), complaints in mobility (adjusted OR 1674200.27, 95% C.I. 4.52 - 619924741831.25, p=0.03), in self-care (adjusted OR 553305.56, 95% C.I. 376.37 - 813413358.35, p< 0.001), and in performing usual activities of daily living (OR 71.57, 95% C.I. 2.87 - 1782.53, p=0.009) at 1-month follow-up, ii) dyspnea (mMRC: B 4.83, 95% C.I. 1.32 – 8.33, p= 0.007) and risk of sarcopenia (SARCF: B 7.12, 95% C.I. 2.17 - 12.07, p=0.005) at 3-month-follow-up and of iii) difficulties in self-care (OR 2746.89, 95% C.I. 6.44 - 1172310.83, p=0.01) at the 6-month-follow-up. In a subgroup of patients (78 individuals) the prevalence of frailty increased at the 1 month follow up compared to baseline (p = 0.009). Conclusion: The precocious identification of frail COVID-19 survivors, who manifest more motor and respiratory complaints during the follow up, could improve the long-term management of these COVID-19 sequelae.